AUDIT SOSIAL ATAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY STUDI KASUS PADA PT. APAC INTI CORPORA BAWEN SEMARANG - Oktaviani Rachmawati Meita (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This research aims to clarify how the implementation of social audits in Corporate Social Responsibility. Object of research is at PT Apac Inti Corpora Bawen Semarang. The data were collected by interview and documentation techniques. The results showed that social audit is a part of the company's strategy phases to be done. Social audit conducted in the form of obtaining such certification ISO 9001, ISO 14001 and PROPER Kementerian Lingkungan Hidup. Social audit was conducted by stakeholders outside the company, it is important to assess whether the activities carried out by the company has been in the interest of all stakeholders. Key words: Social Audit, Corporate Social Responsibility